Prinsip Etika Bisnis Islam Dalam Fatwa Dsn-Mui Tentang Hadiah Dalam Penghimpunan Dana Lembaga Keuangan Syariah - Heni Triwahyuni; Muhajir Muhajir; Fathudin Fathudin (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research looks at the application of Islamic business ethics principles in the DSN-MUI fatwa related to gifts in the fundraising activities of Islamic financial institutions, aiming to maintain integrity and compliance with Sharia law. Using a qualitative method with literature review and descriptive-analytic approach, this research analyzes how the principles of Unity (Tawhid), Equilibrium (Balance), Free Will, and Responsibility are applied in the fatwa. The findings reveal that the DSN-MUI fatwa integrates the values of justice, transparency, and social responsibility in the regulation of gift-giving, ensuring practices that comply with Sharia while supporting the stability and sustainability of Islamic financial institutions. This study offers insightful information for the creation of ethical policies in Islamic finance and serves as a reference for academics and practitioners in addressing moral challenges in business.